On a self-start Darrieus wind turbine: blade design and field tests - Melicio, Rui (2015)
This paper is about a design of an urban area Darrieus VAWT, having self-start ability due to an innovative profile design named EN0005, avoiding the need of extra components or external electricity feed-in. An approach is presented to study the ability of a blade profile to offer self-start ability. Methodologies applied for the blade body and for profile development are reported. Field tests and main conclusions are presented to persuade for the arrangement of this design.